Comparative effects of combined aerobic and resistance training versus high-intensity interval training on insulin resistance, glycaemic control, body composition and quality of life in type 2 diabetes: A 12-week randomised controlled trial - Sampath Kumar Amaravadi; Arthur de Sá Ferreira; Patrícia dos Santos Vigário (PLoS ONE, 2025)
Background Exercise training is a cornerstone in managing type 2 diabetes mellitus (T2DM), yet direct comparisons between combined aerobic–resistance training (A + R) and high-intensity interval training (HIIT) across clinical and patient-reported outcomes remain limited. Objective To compare the effects of A + R and HIIT on insulin resistance, glycaemic control, body composition, physical function, and quality of life in adults with T2DM, relative to standard care. Design and participants A single-centre, randomised controlled trial involving 90 participants with T2DM (aged 30–65 years), allocated to A + R, HIIT, or control groups. Interventions A + R consisted of moderate-intensity aerobic and resistance exercises, while HIIT comprised structured interval sessions. Both programs were delivered 3–5 times weekly for 12 weeks. The control group received usual care without structured exercise. Measurements Primary outcomes included fasting insulin (FI), Glycosylated Hemoglobin (HbA1c), and insulin resistance (HOMA-IR). Secondary outcomes included fasting glucose (FG), 6-minute walk distance (6MWD), subcutaneous and visceral fat, muscle mass, and WHOQOL-BREF domains. Results Compared with control, the HIIT group showed a greater reduction in fasting glucose (Mean Difference [MD] −29.1 mg/dL; 95% CI −41.2 to −17.0) and the A+R group also improved (MD −20.6 mg/dL; 95% CI −31.0 to −10.2). HbA1c was lower versus control in both HIIT (MD −3.35%; 95% CI −4.11 to −2.58) and A+R (MD −3.33%; 95% CI −4.03 to −2.62). Fasting insulin decreased relative to control in HIIT (MD −7.16 mIU/L; 95% CI −10.04 to −4.28) and A+R (MD −8.87 mIU/L; 95% CI −11.77 to −5.97). HOMA-IR improved versus control in A+R (MD −2.33; 95% CI −3.63 to −1.03) with a non-significant trend in HIIT (MD −1.17; 95% CI −2.47 to 0.13). Functional capacity (6-minute walk distance) increased versus control in HIIT (MD +178.9 m; 95% CI 130.5 to 227.4) and A+R (MD +233.6 m; 95% CI 191.8 to 275.5). Body composition favored both interventions: fat-free mass increased (HIIT MD +7.54 kg; 95% CI 4.71 to 10.36; A+R MD +5.96 kg; 95% CI 3.06 to 8.86) while subcutaneous fat (HIIT MD −7.16%; 95% CI −9.33 to −4.99; A+R MD −8.37%; 95% CI −10.65 to −6.09) and visceral fat (HIIT MD −4.70%; 95% CI −5.93 to −3.47; A+R MD −4.58%; 95% CI −5.86 to −3.31) were reduced. Quality of life improved across domains versus control in both groups (e.g., physical domain: HIIT MD +10.29; 95% CI 4.06 to 16.51; A+R MD +13.77; 95% CI 6.62 to 20.91). All results were derived from covariate-adjusted mixed models with multiple comparison corrections (Benjamini–Hochberg FDR, q = 0.05; Bonferroni-adjusted α = 0.002). Limitations Findings are limited to adherent participants, and generalizability is restricted to those without advanced complications. The 12-week duration precludes assessment of long-term sustainability. Conclusion Both HIIT and A+R significantly improved metabolic, functional, and psychosocial outcomes compared with control. HIIT yielded greater benefits for fasting glucose and muscle mass, while A+R conferred broader improvements in HbA1c, fat reduction, and quality of life. These findings support tailoring exercise prescriptions to therapeutic goals and highlight the complementary roles of HIIT and A+R in routine diabetes care. Clinical trial registration The trial is registered with the Clinical Trial Registry of India (reference no: CTRI/2022/04/041762).